CRIANÇAS E ADOLESCENTES VÍTIMAS DE ABUSO SEXUAL E O PROCESSO DE RESILIÊNCIA: PERSPECTIVA DE COMPREENSÃO A PARTIR DA ABORDAGEM ECOLÓGICA DO DESENVOLVIMENTO HUMANO DE BRONFENBRENNER - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2008)
This study focus on development and learning of the resilience by children and adolescents who were victims of sexual abuse by close relatives or their nuclear family’s members. The guide questions were: The local schools and the institution Sentinela Program are developing activities that promote the leaning of the resilience? What are and where are the risks, protection and promoters of resilience factors? The aims of this study were to characterize the educative role of the Sentinela Program and schools to the development and learning of resilience, to identify the risks, protection and promoters of resilience factors. The Bronfenbrenner’s Ecological Theory of Human Development substantiated this research. The data collection was done in Ponta Grossa – Paraná with the Sentinela Program, Tutorial Council and six schools that attend students from 6 to 14 years old. The procedures used were ecological insertion, documentary research, psychological tests application. The instruments of the data collection were reports, interviews, the Childish Stress Scale and H.T.P. Projective and group works. Three children and three adolescents, six professional people from Sentinela Program, thirteen teachers and two tutorial counselors join this work. The phenomenalogical perspective was the analysis device. The outcomes pointed out that two children and three adolescents developed social and emotional resilience; one child developed the academic resilience due to the emotional and pedagogic support from school. It was noticed that there is not educational projects and actions in the schools for the development of the resilience as well as programs for prevention, detection and protection against sexual violence. In the Sentinela Program, the emotional and social resiliences were developed by the learning of social skills about self-control of politeness and expression of positive feelings; by the rescue of the self-esteem, self-confidence and social support to the involved families. The risks factors in the Context Core were: the shortage of information about sexual abuse; few denunciations from schools to the Tutorial Council (three of the six schools did not know about the cases); the lack of communication between schools and the Sentinela Program; the family environment. As protection factors were identified: the creation of the special legal institution that deals with crimes against children and adolescents in Paraná state in 2007; the reference of two cases from schools to the Tutorial Council; the denunciation done by mothers whose daughters were outraged by their companions. The promoter factors of resilience at school, in a case, were the emotional support, reinforcement in school subjects and orientation to the mother’s victim. At Sentinela Program that factor was: the psychological support and accompaniment to five victims; the social attendance to two victims and some pedagogical activities to six. There was some support to the mothers in three cases. Some of the risk factors identified in the Individual Core were low self-esteem in six cases, and suicide thoughts in one case. The self-protection factors consisted in avoiding the aggressor company and believing in the legal punishment. The resilient factors were: friendship for two girls, liking the studies for three and having bonds with confident people for five of them. In the Time Core, living with the aggressor and live in a substandard condition were considered risks factors for three victims. The protection factor, in three cases, was the remoteness from the aggressor. It was noticed that to become resilient, the victims need support and acceptance by the adults who can give them new apprenticeships.
Keywords: resiliência; violência doméstica; abuso sexual; Programa Sentinela; Bronfenbrenner; resilience; sexual abuse; domestic violence; Sentinela Program; Bronfenbrenner; CNPQ::CIENCIAS HUMANAS::EDUCACAO